Impact of formalin and antiseptic contamination on Helicobacter pylori rapid urease test: a prospective study - Nogol Motamedgorji; Mohsen Masoodi; Zahra Rahimi; Emad Jazaa Ghadeer; Nikta Masoodi (Clinical Medicine)
Introduction: The rapid urease test (RUT) is frequently used to diagnose Helicobacter pylori infection in endoscopy patients because of its efficiency, simplicity and high sensitivity. However, RUT accuracy can be compromised by contaminants, such as formalin or glutaraldehyde (GTA), which may lead to false-negative or false-positive results. This study aimed to examine the specific impact of formalin and GTA contamination on RUT reliability for H. pylori detection. Materials and Methods: In this prospective study, 50 patients undergoing upper gastrointestinal endoscopy each provided three gastric biopsies. Each biopsy was processed in one of three distinct RUT solutions: a standard RUT; a formalin-contaminated RUT (prepared by briefly dipping a sterile needle in 10% formalin and then into the RUT); and a GTA-contaminated RUT (prepared similarly with 2.5% GTA). Each sample was evaluated for urease activity (indicated by colour change) after 6 h by a blinded examiner. Results and Discussion: The cohort included 50 patients (52% women, 48% men; mean age 39.5 years), with dyspepsia as the most common symptom (66%). The standard RUT showed a 78% positivity rate, while the formalin-contaminated RUT yielded 0% positivity, and the GTA-contaminated RUT showed a significantly reduced positivity rate of 14%. Conclusion: Direct contamination of RUT solutions with formalin or GTA substantially inhibits urease activity, resulting in false-negative H. pylori results. This highlights the need for rigorous contamination control, including thorough rinsing of biopsy instruments, to prevent diagnostic errors. Adopting standardised washing protocols for endoscopic tools can further ensure reliable RUT outcomes in clinical practice.